Reduced Nhe1 (Na+-H+ Exchanger-1) Function Protects ApoE-Deficient Mice From Ang II (Angiotensin II)–Induced Abdominal Aortic Aneurysms. Issue 1 (July 2020) - Liu, Cong-Lin; Liu, Xin; Wang, Yunzhe; Deng, Zhiyong; Liu, Tianxiao; Sukhova, Galina K.; Wojtkiewicz, Gregory R.; Tang, Rui; Zhang, Jin-Ying; Achilefu, Samuel; Nahrendorf, Matthias; Libby, Peter; et al.
Abstract : IgE-mediated activation of Nhe1 (Na + -H + exchanger-1) induces aortic cell extracellular acidification and promotes cell apoptosis. A pH-sensitive probe pHrodo identified acidic regions at positions of macrophage accumulation, IgE expression, and cell apoptosis in human and mouse abdominal aortic aneurysm (AAA) lesions. Ang II (angiotensin II)–induced AAA in Nhe1-insufficient Apoe −/− Nhe1 +/− mice and Apoe −/− Nhe1 +/+ littermates tested Nhe1 activity in experimental AAA, because Nhe1 −/− mice develop ataxia and epileptic-like seizures and die early. Nhe1 insufficiency reduced AAA incidence and size, lesion macrophage and T-cell accumulation, collagen deposition, elastin fragmentation, cell apoptosis, smooth muscle cell loss, and MMP (matrix metalloproteinase) activity. Nhe1 insufficiency also reduced blood pressure and the plasma apoptosis marker TCTP (translationally controlled tumor protein) but did not affect plasma IgE. While pHrodo localized the acidic regions to macrophage clusters, IgE expression, and cell apoptosis in AAA lesions from Apoe −/− Nhe1 +/+ mice, such acidic areas were much smaller in lesions from Apoe −/− Nhe1 +/− mice. Nhe1-FcεR1 colocalization in macrophages from AAA lesions support a role of IgE-mediated Nhe1 activation. Gelatin zymography, immunoblot, and real-time polymerase chain reaction analyses demonstrated that Nhe1 insufficiency reduced the MMP activity, cysteinyl cathepsin expression, IgE-induced apoptosis, and NF-κB activation in macrophages and blocked IgE-induced adhesion molecule expression in endothelial cells. A near-infrared fluorescent probe (LS662) together with fluorescence reflectance imaging of intact aortas showed reduced acidity in AAA lesions from Nhe-1-insufficient mice. This study revealed extracellular acidity at regions rich in macrophages, IgE expression, and cell apoptosis in human and mouse AAA lesions and established a direct role of Nhe1 in AAA pathogenesis. Abstract : Supplemental Digital Content is available in the text.